2016
DOI: 10.5455/jice.20160217044511
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic and Antioxidant Effect of Cinnamon in poorly Controlled Type-2 Diabetic Iraqi Patients: A Randomized, Placebo-Controlled Clinical Trial

Abstract: Aim:To determine the effect of cinnamon on fasting blood glucose, hemoglobin (Hb) A1c, and oxidative stress markers in poorly controlled type 2 diabetes.Patients and Methods:A total of 25 type 2 diabetic patients of both sexes, aged 49.1 ± 6.0, treated only with hypoglycemic agent sulfonylurea (glibenclamide) were randomly assigned to receive either 1 g of cinnamon or placebo daily for 12 weeks.Results:A highly significant (P ≤ 0.001) reduction (10.12%) of fasting blood glucose level after 6 and 12 weeks of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
36
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 30 publications
5
36
0
2
Order By: Relevance
“…A recent study showed that daily intake of 1g of cinnamon for 12 weeks reduced fasting blood glucose and HbA1c levels in middle-aged type 2 diabetic patients [36]. The antidiabetic effects of cinnamon were reported to increase glucose uptake, improve insulin sensitivity in peripheral tissues, improve glycogen synthesis in the liver, restore pancreatic islets dysfunction, slow gastric emptying rates, and improve diabetic renal and brain disorders through multiple signaling pathways, including the PPARs, PI3K/IRS-1, GLUT4, and Nrf2 pathways [37].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that daily intake of 1g of cinnamon for 12 weeks reduced fasting blood glucose and HbA1c levels in middle-aged type 2 diabetic patients [36]. The antidiabetic effects of cinnamon were reported to increase glucose uptake, improve insulin sensitivity in peripheral tissues, improve glycogen synthesis in the liver, restore pancreatic islets dysfunction, slow gastric emptying rates, and improve diabetic renal and brain disorders through multiple signaling pathways, including the PPARs, PI3K/IRS-1, GLUT4, and Nrf2 pathways [37].…”
Section: Introductionmentioning
confidence: 99%
“…Çalışmamızda en çok kullanılan bitkisel ürün tarçın bulunmuştur. Yapılan çalışmalarda, 12 hafta boyunca 1g tarçın alan tip 2 diyabet hastalarında kan glikozunun ve glikozile hemoglobinin düştüğü ve tarçının antidiyabetik, antioksidan etkilerinin olduğu görülmüştür (10). Yapılan başka bir çalışmada, tarçının 1, 3 veya 6 g günlük alınması serum glukoz, trigliserid, LDL kolesterol, total kolesterol düzeylerini tip 2 diyabetli hastalarda düşürdüğü görülmüştür (11).…”
Section: Introductionunclassified
“…10 Furthermore, recent research indicated that cinnamon intake can reduce FBG and HbA1C levels in type 2 diabetes patients. 11 An experimental study demonstrated that ALA stimulated glucose uptake to a similar extent to insulin in isolated human skeletal myocytes and adipocytes via the activation of the insulin signaling pathway. 38 In addition, ALA appears to have an insulin-sensitizing and lipid-lowering effect in obese individuals predisposed to type 2 diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…10 Moreover, the consumption of cinnamon can reduce FBG and HbA1C among poorly controlled type 2 diabetes patients, as well as improve oxidative stress markers. 11 Alpha-lipoic acid (ALA) is a natural antioxidant. It is known to exert beneficial actions against oxidative stress caused by hyperglycemia.…”
mentioning
confidence: 99%